Is the Impact of Health Shocks Cushioned by Socioeconomic Status? The Case of Low Birthweight - Currie, Janet; Hyson, Rosemary (American Economic Review, 1999)
Is the Impact of Health Shocks Cushioned by Socioeconomic Status? The Case of Low Birthweight by Janet Currie and Rosemary Hyson. Published in volume 89, issue 2, pages 245-250 of American Economic Review, May 1999